Teaching inclusively in higher education - Brown, Susan C.; Fallon, Moira A. (Emerald Publishing Limited : Information Age Publishing Inc., 2010)
This book is designed for higher education instructors. The focus of the book is to assist all faculty instructors in higher education to better meet the needs of their student populations. It addresses the major issue of higher education teaching today: the need to reach all higher education students using active learning strategies. Higher education today is rapidly changing and faculty members are being presented with new types of students: ones who often have clear goals for bettering themselves, but at the same time lack what might have been considered to be basic skills necessary for success in a college or university setting. Instructors today must reach and bring all students into the college or university setting in an inclusive manner. The emphasis of this book is on student-focused strategies for teaching inclusively. This book will provide valuable strategies and practical techniques for instructors to develop inclusive college classrooms that promote the learning of all students.The audience targeted will be all instructors who work with higher education students, including students in community colleges and vocational institutions. The book is designed to be mainly practical instructional strategies with limited theoretical text and references. At the same time, major theories will be included to demonstrate why specific approaches are recommended. Although the authors and editors are from the field of education, the book is particularly valuable for all college instructors without a background in the discipline of education.